1980
DOI: 10.1007/bf01893605
|View full text |Cite
|
Sign up to set email alerts
|

An efficient estimator using auxiliary information

Abstract: The use of ratio and product methods of estimation using auxiliary information for estimating the mean of a finite population is well known. Srivastava [1967] and Reddy [19731 proposed ratio-cum-product type estimators. This paper proposes a transformed estimator which is even more efficient than these estimators for a wide range of the value of the correlation coefficient between the main and auxiliary variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 1 publication
0
23
0
Order By: Relevance
“…In the cases of many repeated surveys and surveys which are based on multiphase sampling techniques, where information is collected on the same variates for several occasions, it is possible to predict the values of certain parameters accurately in advance. Searls (1964), Gleser and Healy (1976) and Lee (1981) have indicated that it is possible to make a close guess for coefficient of variation, whilst Sahai and Sahai (1985) are of the same opinion regarding the guess for correlation coefficient. Murthy (1967, pp.…”
Section: Search Of An Optimum Unbiased Estimator In the Classmentioning
confidence: 95%
“…In the cases of many repeated surveys and surveys which are based on multiphase sampling techniques, where information is collected on the same variates for several occasions, it is possible to predict the values of certain parameters accurately in advance. Searls (1964), Gleser and Healy (1976) and Lee (1981) have indicated that it is possible to make a close guess for coefficient of variation, whilst Sahai and Sahai (1985) are of the same opinion regarding the guess for correlation coefficient. Murthy (1967, pp.…”
Section: Search Of An Optimum Unbiased Estimator In the Classmentioning
confidence: 95%
“…As remarked by Murthy (1967, p. 96) and Sahai and Sahai (1985), these parameters are stable quantities, therefore, these can be known either from the past studies or from the experience gathered in due course Biometrical Journal 41 (1999) 7 of time. The constant w 1 can also be fixed by the experimenter due to familiarity with the population under investigation.…”
Section: The Suggested Class Of Estimatorsmentioning
confidence: 97%
“…For further discussion on this issue, the reader is referred to Murthy (1967), Reddy (1973), Srivenkataramana andTracy (1984) and Sahai and Sahai (1985).…”
Section: Estimators Based On Estimated Optimummentioning
confidence: 99%